Does Physics Forbid Libertarian Freedom? - Koperski, Jeffrey (Filozoficzne Aspekty Genezy, 2022)
Three well-known physicists have recently argued that libertarian freedom is impossible. In their view, free will is incompatible with what we know about science at the most fundamental level. Here I show that their arguments presuppose a naïve version of reductionism and consider two alternatives, one appealing to mind–body dualism and the other to emergentism. The former says that free will is a capacity of one’s mind, an immaterial entity not subject to the laws of nature. The latter says that free will is an emergent capacity that cannot be reduced to the properties of an agent’s constitutive atoms. These alternatives, however, face the same problem: They seem to violate a fundamental law, namely the conservation of energy. I show how the libertarian can respond to this objection.